2011
DOI: 10.3324/haematol.2010.031567
|View full text |Cite
|
Sign up to set email alerts
|

Expression and effects of inhibition of type I insulin-like growth factor receptor tyrosine kinase in mantle cell lymphoma

Abstract: The online version of this article has a Supplementary Appendix. BackgroundType I insulin-like growth factor receptor (IGF-IR) tyrosine kinase induces significant oncogenic effects. Strategies to block IGF-IR signaling are being tested in clinical trials that include patients with aggressive solid malignancies. Mantle cell lymphoma is a B-cell neoplasm with poor prognosis and a tendency to develop resistance. The expression and potential significance of IGF-IR in mantle cell lymphoma are not known. Design and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 58 publications
(51 reference statements)
5
25
0
Order By: Relevance
“…It became evident that the majority of mantle cell lymphoma cell lines and primary tumors show increased IGF2BP3 mRNA expression, in line with IGF2BP3 belonging to the 'mantle cell lymphoma gene expression signature' as reported in a global gene expression profiling study. 6 To a lesser extent and more pronounced in some mantle cell lymphoma cell lines, we found that the IGF 1 and 2 receptors are also expressed on the mRNA level, in concordance with a recent study by Vishwamitra et al 26 These authors demonstrated elegantly that inhibiting the IGF1 receptor by picropodophyllin or short interfering RNA led to decreased viability and proliferation of mantle cell lymphoma cell lines and primary mantle cell lymphoma cells by inducing apoptosis and cell cycle arrest. 26 The rate of tumor cell proliferation has been established as a key biological feature of clinical aggressiveness in mantle cell lymphoma, and several genetic events occurring during the progression of the disease appear to enhance proliferation leading to decreased survival times.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It became evident that the majority of mantle cell lymphoma cell lines and primary tumors show increased IGF2BP3 mRNA expression, in line with IGF2BP3 belonging to the 'mantle cell lymphoma gene expression signature' as reported in a global gene expression profiling study. 6 To a lesser extent and more pronounced in some mantle cell lymphoma cell lines, we found that the IGF 1 and 2 receptors are also expressed on the mRNA level, in concordance with a recent study by Vishwamitra et al 26 These authors demonstrated elegantly that inhibiting the IGF1 receptor by picropodophyllin or short interfering RNA led to decreased viability and proliferation of mantle cell lymphoma cell lines and primary mantle cell lymphoma cells by inducing apoptosis and cell cycle arrest. 26 The rate of tumor cell proliferation has been established as a key biological feature of clinical aggressiveness in mantle cell lymphoma, and several genetic events occurring during the progression of the disease appear to enhance proliferation leading to decreased survival times.…”
Section: Discussionsupporting
confidence: 91%
“…6 To a lesser extent and more pronounced in some mantle cell lymphoma cell lines, we found that the IGF 1 and 2 receptors are also expressed on the mRNA level, in concordance with a recent study by Vishwamitra et al 26 These authors demonstrated elegantly that inhibiting the IGF1 receptor by picropodophyllin or short interfering RNA led to decreased viability and proliferation of mantle cell lymphoma cell lines and primary mantle cell lymphoma cells by inducing apoptosis and cell cycle arrest. 26 The rate of tumor cell proliferation has been established as a key biological feature of clinical aggressiveness in mantle cell lymphoma, and several genetic events occurring during the progression of the disease appear to enhance proliferation leading to decreased survival times. 1 Despite the strong statistical association in our cohort between IGF2BP3 protein expression and an increased Ki-67 index of the tumor cells, the major prognostic marker for survival in previous studies, 22,23 IGF2BP3 expression itself did not correlate with clinical outcome in our analysis reinforcing the idea that the quantitative measurement of tumor cell proliferation in mantle cell lymphoma serves as an integrator of various unfavorable molecular events.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, the cyclolignan PPP, launched as a selective IGF-1R inhibitor [14], has been well tolerated in a phase I/II clinical study and possibly contributed to disease stabilization in four squamous non-small cell lung cancer patients [22]. Although PPP has been suggested as a potential therapy for the B-cell neoplasm multiple myeloma [5,6] and for different classes of lymphoma [7][8][9][10], there are no reports investigating the potential benefits of using PPP against DLBCL.…”
Section: Discussionmentioning
confidence: 87%
“…Among the lymphohematopoietic cancers, the IGF-1R has been suggested to represent a therapeutic target in multiple myeloma [4][5][6], T cell ALK? anaplastic largecell lymphoma [7], T lymphoblastic leukemia/lymphoma [8], mantle cell lymphoma [9] and classical Hodgkin lymphoma [10].…”
Section: Introductionmentioning
confidence: 99%